Pemanfaatan Batu Sungai Pucak dengan Filler Abu Sekam Padi untuk Lapis AC-BC - Rio Patrick Febryan Pude; Robert Mangontan; Alpius (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
Road pavement is an important factor supporting the development of transport infrastructure. The asphalt concrete mixture on the road needs to be reinforced with filler material to increase the strength of the asphalt mixture. Therefore, cheaper alternative filler materials such as rice husk ash can be used in asphalt mixtures. This study aims to understand and determine the characteristics of the AC-BC layer mixture using aggregates from the Pucak River with the substitution of rice husk ash filler. The methodology of this study is designed to determine the utilization of rice husk ash waste as a filling material in an AC - BC layer mixture. The research method used in this study includes testing the specific gravity of rice husk ash filler which is followed by designing the composition of the AC-BC mixture with the substitution of rice husk ash filler then continued with Conventional Marshall testing. The results showed that the test object with a rice husk ash content of 0% - 75% using an asphalt content of 5.00% met the 2018 Bina Marga General Specifications. From the test results, it can be concluded that rice husk ash can be used as a partial substitution of cement filler for AC-BC layers where all the requirements listed in the 2018 Bina Marga General Specification have been met.